2017
DOI: 10.1111/1471-3802.12407
|View full text |Cite
|
Sign up to set email alerts
|

Varying access to professional, special educational support: a total population comparison of special educators in Swedish independent and municipal schools

Abstract: Independent schools are securely established in the Swedish education system. Prior research shows they generally have fewer pupils in need of support and lower proportions of special educators. Here, results are presented from a total population study of Swedish special educators (n = 4252) examined after 2001. The aim was to explore and compare the occupational situations of special educators working in Swedish municipal and independent schools. This is done by studying their occupational situations and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
0
14
0
3
Order By: Relevance
“…A survey to all independent comprehensive schools in Sweden showed that 15.2% of the independent schools stated that they had refused admittance to students with special educational needs in a three year period. Additionally, the proportion of pupils in need of support varied considerably depending on the profile of the independent schools (Magnússon, Göransson and Nilholm, 2014;Magnússon, 2015) and there are reports that independent schools provide special educational resources to a much lower degree than schools run by the municipalities (Magnússon, 2015;Magnússon, Göransson, & Nilholm, 2017;Ramberg, 2015). The results indicated that the choice of schools is limited for pupils in need of special support compared to other pupil groups (see also, Göransson et al, 2012).…”
Section: The Current Context Of Swedish Educationmentioning
confidence: 99%
“…A survey to all independent comprehensive schools in Sweden showed that 15.2% of the independent schools stated that they had refused admittance to students with special educational needs in a three year period. Additionally, the proportion of pupils in need of support varied considerably depending on the profile of the independent schools (Magnússon, Göransson and Nilholm, 2014;Magnússon, 2015) and there are reports that independent schools provide special educational resources to a much lower degree than schools run by the municipalities (Magnússon, 2015;Magnússon, Göransson, & Nilholm, 2017;Ramberg, 2015). The results indicated that the choice of schools is limited for pupils in need of special support compared to other pupil groups (see also, Göransson et al, 2012).…”
Section: The Current Context Of Swedish Educationmentioning
confidence: 99%
“…A government report in the early 2000s (SNAE [The Swedish National Agency for Education] 2003) concluded that independent schools were more satisfied (than municipal schools) with their organisation of special education, with the resources Giota and Emanuelsson 2011Göransson, Magnússon, and Nilholm 2012Magnússon 2015Magnússon 2016Magnússon, Göransson, and Nilholm 2014Magnússon, Göransson, and Nilholm 2017Ramberg 2013Ramberg 2014Ramberg 2015Tah 2018 allocated for special support, and that independent schools had higher goal attainment. The report also described the independent schools as innovative as regards the organisation of special education.…”
Section: Organisational Conceptualisation Of Special Education and Inmentioning
confidence: 99%
“…As mentioned above, special needs educators (SNEs) are considered important professions when it comes to organising special education and developing inclusive education. However, primary-and secondary-independent schools employ SNEs to a much lower degree than schools run by municipalities (Magnússon 2015;Magnússon, Göransson, and Nilholm 2017;Ramberg 2013Ramberg , 2015. Only 50% of SNEs working in independent primary schools have full-time positions as SNEs, compared to 80% of SNEs in municipal schools.…”
Section: Resources and Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Abbott 2007;Cole 2005;Lindqvist 2013;Lingard 2001;Pearson 2008;Szwed 2007;Takala, Pirttimaa, and Törmänen 2009) and their roles and jurisdiction is often poorly defined (e.g. Göransson, Lindqvist, and Nilholm 2015;Lindqvist et al 2011;Magnússon, Göransson, and Nilholm 2017).…”
Section: Introductionmentioning
confidence: 99%